Time- and temperature-dependent molecular responses to UV-filter 2-ethylhexyl salicylate revealed by dose-dependent yeast functional genomics - Zitong Wu; Shasha Zhang; Ruyuan Xu; Yifei Guo; Yuxin Zhang; Linhao Zong; Fei Ma; Xiaowei Zhang; Miao Guan (Environmental Pollution, 2026)

Unraveling the molecular mechanisms of triphenyl phosphate-induced hepatotoxicity: Integrated insights from network toxicology, molecular docking, and transcriptomic evidence - Ke Fan; Yifei Guo; Qiuxia Zhang; Shasha Zhang; Xin Ni; Yuxin Yang; Jiayi Zhang; Dong Chen; Linhao Zong; Miao Guan (Food and Chemical Toxicology, 2026)

miR-203 Alleviates Myocardial Damage Caused by Acute Coronary Syndrome by Inhibiting CA125 - Yanfang Guo; Jinlin Li; Linhao Zhang (Biochemical Genetics, 2026)

Evaluation and prediction of atmospheric environmental carrying capacity in an Inland urban agglomeration in northern China - Zhongxiu Zhen; Linhao Guo; Fei Xie; Liang Li; Xingjun Zhou; Chunyu Wu; Frank Yonghong Li; Jinyuan Xin; Changwei Lü (Atmospheric Research, 2026)

Metabolism study of two phenethylamine − derived new psychoactive substances using in silico, in vivo, and in vitro approaches - Yiling Tang; Linhao Xu; Zhenshuo Guo; Junbo Zhao; Yue Xiao; Ping Xiang; Lili Xu; Hui Yan (Archives of Toxicology, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Hybrid Transition of Subseasonal Atmospheric Regimes and Its Impact on the Extreme ‘West Cold‐East Warm’ Mode in North America - Ruiwei Guo; Yao Yao; Jiaqi Shi; Binhe Luo; Dehai Luo; Linhao Zhong (International Journal of Climatology, 2025)
On February 22, 2023, North America experienced an unusual weather phenomenon characterised by extreme cold in the west and extreme warmth in the east, reflecting a surface air temperature (SAT) seesaw pattern that significantly impacted human activities in the region. Utilising reanalysis data, we analysed this case as well as similar events in long‐term climate records. The results indicate that this extreme temperature mode is caused by a hybrid evolution of atypical North Pacific Oscillation (NPO) and Pacific‐North American (PNA) phase relationships, transitioning from a dominant positive NPO phase to a strong negative PNA phase, while maintaining and developing Pacific blocking, which we refer to as a hybrid transition of atmospheric regimes. Further analysis revealed that the anomalously weak meridional potential vorticity gradient (PVy) in southern Alaska prior to the event provided favourable conditions for the northward movement and intensification of the anticyclone in the central North Pacific, serving as a key driving factor for the transition of circulation mode from positive NPO to negative PNA. Additionally, significant anomalous outgoing longwave radiation (OLR) in the tropical Indian Ocean prior to the event indicated enhanced convective activity in that region, which may have triggered meridional Rossby waves, thereby influencing the transition between NPO and PNA in mid to high latitudes. Thus, the anomalous PVy in southern Alaska and the OLR from the tropical Indian Ocean may serve as potential precursor indicators for such extreme weather events.

Negative carbon emission power generator: A combination of high temperature proton exchange membrane fuel cell and absorption carbon capture system - Chaohuan Tan; Linhao Cheng; Wanli Peng; Hanxin Yang; Rongxiang Luo; Juncheng Guo (Journal of Cleaner Production, 2025)

Achieving layered deposition of lithium by uniform Li-ion flux distribution in grids - Liguang Qin; Shaomin Zhang; Bo Zhang; Shangqi Sun; Ze Sun; Aiguo Zhou; Linhao Xin; Chang Guo (Chemical Engineering Journal, 2025)

The intensifying relationship between heatwaves in the mid–lower reaches of the Yangtze River valley and the upstream atmospheric wave train after the 2000s - Jiaqi Shi; Yao Yao; Ruiwei Guo; Binhe Luo; Linhao Zhong (Atmospheric Research, 2025)

Photothermal synergistic catalytic hydrogen production from glycerol based on spectral beam splitting coating: A novel full solar spectrum utilization strategy - Dongqiang Lei; Yue Lv; Bin Zhao; Linhao Wang; Ruishen Guo; Zhifeng Wang (Fuel, 2024)